DETECTION OF HETEROTROPHIC AND COLIFORM BACTERIA IN TWO RIVERS IN SIDOARJO REGENCY, INDONESIA: BUNTUNG AND SINIR RIVERS - YACHYA, ARIF; Zaki, Ekiq Naufal; Herdina, Abelya Putri; Astuti, Yola Amanda; Azmi, Nabila Afni Ulul; Wakhyuni, Indah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2023)
The Buntung and Sinir Rivers are located in Sidoarjo Regency, East Java. Until now, both rivers have been used by residents for their daily activities. Therefore, for the safety and health of residents living around these two rivers, it is necessary to carry out HPC (heterotrophic plate count) and coliform tests. The method used is the pour plate and MPN (Most Probable Number) series 5-5-5 tubes. The HPC test results showed that the population of heterotrophic bacteria in the Buntung and Sinir River water samples was 9,5,103 and 7,2,104 CFU/mL, respectively. The MPN values for total coliforms from Buntung and Sinir river water samples were 33.103 and 109.103 CFU/100 mL, respectively. The MPN values for fecal coliforms and E. coli are the same. The MPN values of fecal coliform and E. coli for Buntung and Sinir river water samples were 17.103 and 12.103 CFU/100 mL, respectively. These results show that the Buntung and Sinir Rivers are polluted by organic materials and feces. The population of heterotrophic bacteria and the total MPN coliform, fecal, and E. coli values for both river waters exceed the microbiological standards of Minister of Health Regulation Number 2 of 2023 and Republic of Indonesia Government Regulation Number 22 of 2021, so it is not suitable for daily activities.